Audit opinion research: overview and research agenda - Nurhidayah Nurhidayah; Made Sudarma; Ali Djamhuri; Sari Atmini (Cogent Business & Management, 2024)
The purpose of this study was to trace the evolution of audit opinion research and identify research gaps that require the future investigation. Data was collected from Scopus and Dimension sources and then filtered by criteria so that the total final data analyzed bibliometrically was 709 over the last ten-year observation period. The research method is carried out in two stages, namely bibliometric analysis and content analysis on relevant articles. This study finds that the majority of audit opinion research have examined the topics of audit quality, types of audit opinions, business continuity, financial ratios, shopping opinions, earning management, audit tenure, and audit fees. Many audit opinion studies have employed quantitative methods, while a small number have used qualitative research methods. Furthermore, previous audit opinion studies have focused on corporate research, especially companies listed in the stock exchange market. Audit opinion research have also been explored in the local government sector, while they, in the relation to education, health, and sharia institutions still need to be improved. This research documents valuable research insights to future research agendas. In addition, the results revealed flaws in the audit opinion study of untouched objects.
Keywords: M42; M49; 650; Audit opinion; bibliometrics; audit; research agenda